Metodologi Studi Islam - Wafiq Azizah; Anri Anggraeni Iqbal; Abbas (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
ABSTRACT This study aims to examine the methodology of Islamic studies as a scientific approach in understanding Islamic teachings comprehensively and contextually. One of the main problems in contemporary Islamic studies is the tendency toward partial and purely textual understanding, which limits the relevance of Islamic teachings in modern life. This research employs a qualitative approach using library research methods by analyzing books, scientific journals, and relevant academic literature related to Islamic studies methodology. The results indicate that the methodology of Islamic studies encompasses various paradigms and approaches, including normative-theological, historical, sociological, and philosophical approaches, which complement one another in building a holistic understanding of Islam. The integration of textual and contextual approaches is essential to produce analytical, critical, and adaptive Islamic scholarship. Therefore, a proper methodological framework enables Islamic studies to address contemporary challenges and strengthens the role of Islam as a source of guidance in both academic and social contexts.